2015
DOI: 10.1007/s10815-015-0470-x
|View full text |Cite
|
Sign up to set email alerts
|

Female offspring sired by diet induced obese male mice display impaired blastocyst development with molecular alterations to their ovaries, oocytes and cumulus cells

Abstract: Purpose To investigate the impacts that a paternal high fat diet (HFD) has on embryology, ovarian/cumulus cell gene expression and COC metabolism from female offspring, using a mouse model. Methods Founder male mice were either fed a control diet (CD) or a HFD for 12 weeks. The HFD induced obesity but not diabetes, and founder males were then mated to normal weight CD fed female mice. Female offspring were maintained on a CD, super-ovulated, mated and the resultant zygotes were cultured to the blastocyst stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…23 Studies in the mouse are showing that the mother's metabolic status at the time of conception may impact the metabolic profile of the next generation and also the ovarian reserve and physiology. 24 A similar phenomenon was also described in cows by Walsh et al 25 and was also demonstrated in rats. 26 The reduced energy diet around conception and for 100 days post artificial insemination (AI) resulted in heifer calves with diminished ovarian reserves at 2 years of age 27 and potentially reduced fertility.…”
Section: The Epigenomesupporting
confidence: 69%
“…23 Studies in the mouse are showing that the mother's metabolic status at the time of conception may impact the metabolic profile of the next generation and also the ovarian reserve and physiology. 24 A similar phenomenon was also described in cows by Walsh et al 25 and was also demonstrated in rats. 26 The reduced energy diet around conception and for 100 days post artificial insemination (AI) resulted in heifer calves with diminished ovarian reserves at 2 years of age 27 and potentially reduced fertility.…”
Section: The Epigenomesupporting
confidence: 69%
“…32 F1 female mice, born to diet-induced obese fathers, had disrupted fertility with altered ovarian genes and delayed embryo development. 33 These studies confirm the transmission of disease across generations and in a specific manner of mode of transmission. It is clear in the present study there is no transmission of poor bone health to female offspring via the paternal line.…”
Section: Paternal Line Bone Outcomesmentioning
confidence: 55%
“…Apart from mtDNA mutations, mitochondrial damage in oocytes has also been linked with increased risk of metabolic diseases in offspring. Obesity leads to increased lipid content in the follicular fluid, cumulus cells, and oocytes, which in turn damage organelles such as mitochondria and the ER (Wang et al, 2009;Wu et al, 2010;Fullston et al, 2015;Ruebel et al, 2017). Impaired ER function can lead to activation of the unfolded protein response (UPR) and Ca +2 release, further disrupting mitochondrial function (i.e., decreased Dym and increased ROS) and oocyte homeostasis (Wu et al, 2010(Wu et al, , 2015Luzzo et al, 2012;Hou et al, 2016).…”
Section: Transmission Of Metabolic Diseases Linked To Mitochondria Dymentioning
confidence: 99%